How Does Personalization in News Stories Influence Intentions to Help With Drought? Assessing the Influence of State Empathy and Its Antecedents - Wald, Dara M.; Johnston, Erik W.; Wellman, Ned; Harlow, John (Frontiers in Communication, 2021)
Personalized stories are a powerful tool for communicating about science, particularly when a scientific topic is complex or unfamiliar. One example of such a topic is drought, something many regions of the world face regularly. Like other environmental challenges, drought recovery efforts benefit from a mobilized collective response through prosocial action, including volunteering and donations. The objective of this study was to examine how storytelling about drought influences emotional responses and empathic processes that in turn contribute to prosocial action. Using data collected from an online survey (N = 249) with undergraduate students, the current study tests the hypothesis that, relative to non-personalized stories, personalized news stories about drought will increase audiences’ cognitive and emotional responses, including perceived suffering, narrative engagement, and state empathy. In addition, this study examines how emotional responses to personalized news stories influence readers’ intentions to donate to farmers suffering from drought. Results reveal that personalized news stories are more likely than non-personalized stories to increase readers’ state empathy and perceptions of others’ suffering. Perceived suffering was directly related to the affective and cognitive dimensions of state empathy. Narrative engagement (i.e., transportation) was also directly related to the affective and cognitive dimensions of state empathy and indirectly associated with intentions to donate to assist those suffering from drought. Affective state empathy was directly associated with donation intentions, suggesting that an emotional response to media portrayals of suffering may promote prosocial intentions. We discuss the potential implications for using personalized news stories about drought and other natural disasters to motivate prosocial action.